Methodics of teaching polynomial approximation of functions in CAS enviroment - Dabrišienė, Vilija; Šileikienė, Regina Dalytė (Lietuvos matematikos rinkinys, 2023)
A number of changes have taken place in recent years, which have influenced teaching mathematics at university level. Most important two are: we have to cope with the influx of students whose background knowledge and motivation is very low; and we have to cope with teaching of following students in CAS environment. Alas there is no many methodics based on research existing. So, we present our methodics for teaching Polynomial approximation of functions in CAS environment: concept assumptions, fragments of methodic materials and results of validation of these methods.
Keywords: teaching in CAS enviroment